Performance evaluation of bus routes - Brochado, Ana Oliveira (2010)
Existing approaches in the literature have mainly measured performance of transit agencies or whole transit systems. Nevertheless, the challenge for decision-makers remains on how to focus on disaggregated performance measurement. This works intends to present a methodology designed to evaluate the performance within corridors (bus routes). As the performance of a route should be compared with operating routes in similar environments, we first propose a classification of 78 lines which integrate the public transport system in OPORTO city. Such classification is conducted based on physical features, demand characteristics, and supply indicators as well as making the use of cluster analysis techniques. We have concluded that the obtained groups could be ranked and are associated with different levels of financial performance measures. It is also anticipated that this disaggregate performance evaluation could provide decision-makers with operational insights as how to improve the performance of the bus network as a whole